2017
DOI: 10.11646/zootaxa.4282.1.1
|View full text |Cite
|
Sign up to set email alerts
|

MtDNA differentiation and taxonomy of Central Asian racerunners of Eremias multiocellata-E. przewalskii species complex (Squamata, Lacertidae)

Abstract: We provide an integrative analysis of the diversity of the E. multiocellata—E. przewalskii species complex in Central and Middle Asia using morphological and molecular (COI DNA-barcoding) data. We report preliminary data on mtDNA variation within this group and clarify the taxonomic status and distribution of the members of the species complex. We also provide a description of a new Eremias species from Eastern Kazakhstan and western Mongolia, where it occurs in sympatry with E. multiocellata sensu stricto, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 805 publications
(29 citation statements)
references
References 32 publications
5
24
0
Order By: Relevance
“…Fifteen of the 26 native Mongolian amphibian and reptile species (Terbish et al 2006, Orlova et al 2014, 2017 The material tentatively identified by us as Eremias przewalski (Appendix) correspond to at least two different lineages based on the molecular results of Orlova et al (2017). The ID165 likely correspond to the lineage considered as E. cf.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Fifteen of the 26 native Mongolian amphibian and reptile species (Terbish et al 2006, Orlova et al 2014, 2017 The material tentatively identified by us as Eremias przewalski (Appendix) correspond to at least two different lineages based on the molecular results of Orlova et al (2017). The ID165 likely correspond to the lineage considered as E. cf.…”
Section: Discussionmentioning
confidence: 87%
“…przewalski, while ID 168 would correspond to the clade named as "E. cf. reticulata" by Orlova et al (2017). The specific affinities of the other revisited populations remain uncertain; however, ID 167 is geographically close to populations of E. przewalski sensu stricto.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations